2021
DOI: 10.1097/hco.0000000000000867
|View full text |Cite
|
Sign up to set email alerts
|

Endocan: a new marker of endothelial function

Abstract: Purpose of reviewTo consider the role of endocan as an inflammatory marker in cardiovascular diseases. Recent findingsEndocan, an endothelial inflammatory marker, is associated with cardiovascular disease. SummaryVascular endothelial inflammation plays a key role in the pathogenesis of inflammatory and cardiovascular diseases by influencing thrombogenesis, tumour invasion and secretion of bioactive mediators. We discuss the role of endocan mainly in the context of cardiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
0
8
0
2
Order By: Relevance
“…ESM1 is a 50 kDa soluble proteoglycan and is mainly secreted by vascular endothelial cells. In normal tissues, ESM1 is mainly expressed in vascular endothelial cells, distal renal tubular epithelial cells, and pulmonary endothelial cells, and is mainly involved in the in ammatory response [32] and angiogenesis [33]. Accumulative studies have shown that ESM1 was hyper-expressed in a variety of malignancies and was associated with tumor prognosis [34].…”
Section: Discussionmentioning
confidence: 99%
“…ESM1 is a 50 kDa soluble proteoglycan and is mainly secreted by vascular endothelial cells. In normal tissues, ESM1 is mainly expressed in vascular endothelial cells, distal renal tubular epithelial cells, and pulmonary endothelial cells, and is mainly involved in the in ammatory response [32] and angiogenesis [33]. Accumulative studies have shown that ESM1 was hyper-expressed in a variety of malignancies and was associated with tumor prognosis [34].…”
Section: Discussionmentioning
confidence: 99%
“…ESM1 is a 50 kDa soluble proteoglycan and is mainly secreted by vascular endothelial cells. In normal tissues, ESM1 is mainly expressed in vascular endothelial cells, distal renal tubular epithelial cells and pulmonary endothelial cells, and is mainly involved in the in ammatory response [33] and angiogenesis [34]. Accumulative studies have shown that ESM1 was hyper-expressed in a variety of malignancies and is associated with tumor prognosis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial Cell-Specific Molecule 1 (Endocan) is a new immunoinflammatory marker that may be associated with cardiovascular events. 68 Some cardiovascular diseases and related conditions, are associated with raised endocan levels. 69 Furthermore, it is possible that endothelial injury, activation, and dysfunction are caused by oxidative stress in the relationship between the HT and endothelial dysfunction.…”
Section: Atherosclerosis Markers and Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%